Pemanfaatan Teknologi Digital dan Kecerdasan Buatan dalam Menunjang Ekonomi Desa Melalui UMKM - Irwan, Andesta Granitio; Wahyuzi, Zikri; Dalimunthe, Nurzaidah Putri; Martahayu, Vika; Juliansyah, Ari (Jurnal Pengabdian Masyarakat Waradin, 2025)
The village economy supported by MSMEs is very important for the progress of a village, especially in the islands, but limited access provides minimal opportunities for MSMEs to develop. Kumbung Village, located in South Bangka Regency, is one of the villages that has the above problems, therefore in increasing the competence of MSMEs, it is necessary to socialise the potential and use of digital technology, especially the use of intelligence that is relatively easy and inexpensive to use. Community service activities are carried out at the Kumbung Village Office with the target of village officials and the community, especially technology-savvy teenagers. The community service programme focused on the use of artificial intelligence in designing strategies to improve the quality of MSMEs and explore the potential of the village that can support the economy of residents. In the service programme, the practice of using Gemini.Ai was carried out to find the potential of MSMEs, making logos as product branding, and marketing strategies. The results obtained were the addition of skills of socialisation participants related to the use of Gemini.Ai in providing ideas and strategies as well as branding village MSME products with positive results and participants understood the advantages and disadvantages in the Gemini.Ai application in providing assistance for the marketing process of MSME products.